Integrating Planned Behavior and Technology Acceptance Models: A Study of GoFood after COVID-19 - Margaret, Felicia; Sidharta, Helena (Bina Nusantara University, 2023)
One of the most apparent changes due to COVID-19 pandemic was the increase in the utilization of online food delivery services. An in-depth analysis was needed to find the fundamental aspects behind this change that make online food delivery services an integral part of people’s lifestyles even after the pandemic. The research aimed to explore the determinants of customers’ intention to use GoFood (IU) by integrating the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB) to construct the research model. The research novelty was reflected through convenience motivation, which was crucial in enhancing the intention to use GoFood. This was achieved by exploring the interaction between the TAM and TPB. The underlying factors behind customers’ intention to use GoFood were defined by price-saving orientation (PSO) and timesaving orientation (TSO) with a mediating variable called convenience motivation (CM). Afterward, 252 valid questionnaires from respondents who live in Surabaya and Sidoarjo were collected using thesnowball sampling method and analyzed using the SEM-PLS method. The result reveals that PSO is the most significant factor behind the intention to use (IU). Meanwhile, TSO only indirectly affects IU, which means it will only be impactful when mediated by CM. Moreover, CM itself has a significant impact on IU.